Effect of Occupational Safety and Health (K3) and Work Motivation on Employee Performance at Rumah Batik Tulis Al-Huda Sidoarjo - Akbar, Mochamad Andre Prawira; Kustini, Kustini (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This research aims to find out the effect of Occupational Safety and Health (K3) and Work Motivation on Employee Performance at Rumah Batik Tulis Al-Huda Sidoarjo. This research uses a quantitative method with a saturated sample technique of 55 respondents. The analysis technique used in SMART PLS. The results showed that K3 and work motivation had a positive and significant impact on employee performance at Rumah Batik Tulis Al-Huda Sidoarjo.